Pengaruh Penelusuran Hedonis dan Penelusuran Utilitarian pada Dorongan Pembelian Impulsif Konsumen Papan Pasar Daring - Santi Budiman; Eny Sulistyowati (Universitas Mercu Buana Yogyakarta, 2024)
The purpose of this study was to determine the situational factors that make consumers who use the market board application dare to have the urge to make impulsive purchases. This was done because impulsive buying is the most common behavior in purchasing. The research model consists of interpersonal influences, visual appeal, portability, hedonic search, and utilitarian search. Furthermore, hedonic search and utilitarian search on impulse buying drives. Sampling in this study used non-probability with a purposive sampling technique. The sample size was 203 respondents. The data collection technique in this study used a questionnaire distributed online according to predetermined criteria, namely mobile device users in accessing the online market board application, and having made at least one purchase in the last six months. The data analysis method used is Structural Equation Modeling (SEM). The findings of this study indicate that interpersonal influences affect both hedonic and utilitarian search activities, visual appeal does not affect hedonic search but does affect utilitarian search, portability does not affect hedonic search, but does affect utilitarian search. Utilitarian search has no effect on impulse buying drive, and hedonic search has an effect on impulse buying drive.